Takotsubo syndrome with transient obstruction of the left ventricle outflow tract: A case report - Dmitrii S. Maznev; Dmitrii S. Evdokimov; Ekaterina D. Evdokimova (КардиоСоматика)
BACKGROUND: Modern data have expanded our understanding of the pathogenetic mechanisms and clinical and laboratory findings in a patient with Takotsubo syndrome (TS). Nonetheless, its timely diagnosis and treatment remain challenging. All patients are initially treated according to the acute coronary syndrome protocol, with a "working" diagnosis of myocardial infarction without an obstructive lesion in the coronary arteries. However, the treatment of in-hospital complications of TS has its limitations and specific features.